Constructing featured supereulerian graph. (17th November 2022) - Algefari, Mansour J.
Abstract: A graph is supereulerian if it has a spanning eulerian subgraph. In this paper we construct a supereulerian graph controlling its matching number, minimum degree and edge connectivity, where δ ( G ) < α ′( G )